The Role of Parental Emotional Intelligence in Enhancing Children's Resilience After Divorce: An Analysis Based on Maqāṣid al-Sharī‘ah - Sairatun Nida; M. Rafli Kurniawan; Arif Sugitanata (Institut Agama Islam Nahdlatul Ulama Tuban, 2024)
Divorce has become a significant social phenomenon, impacting not only the couple but also the children involved in the process. This research aims to explore the role of parental emotional intelligence in enhancing children's resilience post-divorce, using the Maqāṣid al-Sharī‘ah framework for analysis. Previous studies have primarily focused on external factors such as social support, co-parenting, and intervention programs in fostering children's resilience. However, this study shifts the focus toward parents' internal abilities, particularly their emotional intelligence in managing emotions and its direct impact on children. Utilizing a literature review and qualitative research with a descriptive-analytical approach, this study examines data from academic literature, journals, books, and related reports. The findings show that parental emotional intelligence plays a crucial role in maintaining children's emotional stability, thereby reducing the negative effects of divorce on their psychological, social, academic, and financial well-being. Additionally, the application of Maqāṣid al-Sharī‘ah introduces a religious and spiritual dimension to emotional intelligence, emphasizing the protection of life, intellect, and lineage. Parents with high emotional intelligence are not only able to manage conflicts healthily but also create an environment that supports the emotional and social development of their children. This research contributes to the academic discourse by integrating psychological and spiritual aspects into post-divorce parenting and offers practical implications for parents to enhance their emotional intelligence for the future well-being of their children.